Preparing an electronic plan to implement the artistic gymnastics curriculum for the first-stage students of the Department of Physical Education in the College of Basic Education (Journal of the College of Basic Education, 2022)
The research included five chaptersChapter One: This chapter includes the introduction and the importance of the research: through joint cooperation with some telecommunications companies, to ensure the provision of programs for distance education and open education, by means of the mobile phone, or using it as a source of modern learning resources that can be added to the system of e-learning resources provided by the institutions The importance of the research lies in shedding light on some aspects related to the use of the mobile phone in the implementation of the artistic gymnastics curriculum as one of the new forms in education, and the obstacles to its adoption, by trying to identify the factors that helped the emergence and spread of this type of education, and its concept, characteristics, and application requirements.